Regression Analysis Video Tutorials to Improve College Students' Data Analysis Skills - Noor, Widya Noviana; Wulansari, Widi (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
To improve the quality of education in terms of data analysis, a learning innovation is needed. Moreover, in learning statistics, the requirements for complicated calculations require an innovative product that can overcome these problems. The purpose of this research is to develop video tutorials on regression analysis to improve students' data analysis skills. The type of research that has been carried out uses RnD (Research and Development) research with a quantitative approach. The subjects of this study were students in two university as the site for the limited trial, and two university as the site for the large group trial. The analysis uses 2 designs: a pretest-posttest group design and a posttest-only design with a nonequivalent group. The results of this study indicate that video tutorials are suitable for students in carrying out simple linear regression analysis, and this research implies that students who use video tutorials in carrying out simple linear regression analysis have better skills than those who do not. Thus it can be concluded that video tutorials on regression analysis are able to improve students' data analysis skills.